Inventarisasi Tumbuhan Paku (Pteridophyta) di Dusun Oelmuke, Desa Tasinifu, Kecamatan Mutis Kabupaten Timor Tengah Utara, Provinsi Nusa Tenggara Timur - Dicky Frengky Hanas; Emilia Juliyanti Bria; Ite Morina Yostianti Tnunay (Fakultas Pertanian, Universitas Timor, 2019)
The distributon of Fern plant (Pterydophyta) in Indonesia is very wide, inculded in Oelmuke Village. However, the information about the existence of fern plant was very limitid even though this information important for utilization and conservation. This research aimed to inventory fern in Oelmuke Village. The result showed that there are 11 ferns spesies from 9 family, are Aspleniaceae, Davalliaceae, Dennstaedtiaceae, Equisetaceae, Neprolepidaceae, Polypodiaceae, Psilotaceae, Pteridaceae, and Thelypteridaceae. Polypodiaceae is dominant family in Oelmuke Village.